2008
DOI: 10.1128/iai.00045-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Two Novel Staphylococcal Enterotoxins, Types S and T

Abstract: In addition to two known staphylococcal enterotoxin-like genes (selj and selr), two novel genes coding for two superantigens, staphylococcal enterotoxins S and T (SES and SET), were identified in plasmid pF5, which is harbored by food poisoning-related Staphylococcus aureus strain Fukuoka 5. This strain was implicated in a food poisoning incident in Fukuoka City, Japan, in 1997. Recombinant SES (rSES) specifically stimulated human T cells in a T-cell receptor V␤9-and V␤16-specific manner in the presence of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
173
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 34 publications
4
173
0
Order By: Relevance
“…This leads to a massive release of proinflammatory cytokines and contributes to the severity of S. aureus sepsis (McCormick et al 2001;Holtfreter and Broker 2005). To date, 21 SEs have been identified based on sequence homologies (Becker et al 2003;Ono et al 2008). Although a few clinical studies have attempted to correlate toxic shock and outcome with the presence of certain SEs in patients with S. aureus infections (Kravitz et al 2005;Ferry et al 2008), the contribution of these toxins to outcome is still unclear.…”
mentioning
confidence: 99%
“…This leads to a massive release of proinflammatory cytokines and contributes to the severity of S. aureus sepsis (McCormick et al 2001;Holtfreter and Broker 2005). To date, 21 SEs have been identified based on sequence homologies (Becker et al 2003;Ono et al 2008). Although a few clinical studies have attempted to correlate toxic shock and outcome with the presence of certain SEs in patients with S. aureus infections (Kravitz et al 2005;Ferry et al 2008), the contribution of these toxins to outcome is still unclear.…”
mentioning
confidence: 99%
“…The percentage of isolates producing enterotoxin type A was low. Currently, more than 20 types of staphylococcal enterotoxins are known (Balaban and Rasooly, 2000;Pereira et al, 1991;Munson et al, 1998;Orwin et al, 2001;Omoe et al, 2005;Thomas et al, 2006;Ono et al, 2008). However, enterotoxin A is the most commonly staphylococcal enterotoxin associated with foodborne outbreaks, followed by enterotoxin D (Balaban and Rasooly, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In 2001, a cluster of genes with homologies to SE genes was identified and named the enterotoxin gene cluster (egc). Since many of the genes produced SE-like proteins, Jarraud et al (2001) suggested that the gene cluster formed an enterotoxin nursery where genomic rearrangements would lead to new SEs, a fact that has now been confirmed with the development of the new exotoxin SEG (Lindsay, 2011;Thomas et al, 2006 (Uchiyama et al, 2003;Ono et al, 2008) b Gene location of the toxin c enterotoxin gene cluster d Staphylococcus aureus phatogeniciti islands Table 1. Staphylococcal enterotoxin/superantigens…”
Section: Genetic Analysis Of Se Genesmentioning
confidence: 99%
“…Using the Clustal W program, the amino acid sequences of the SEs were aligned and evolutionary distances determined. A dendrogram constructed by the near neighbor-joining method divides the toxins into three major and two minor monophyletic groups (Ono et al, 2008;Uchiyama et al, 2003). The first two groups contain the classical toxins SEA, SED, SEE (Group 1) and SEB, SEC (Group 2) in addition to newly identified SEs; Group 3 contains only newly identified toxins.…”
mentioning
confidence: 99%